Basic properties of solutions of fuzzy differential equations (Nonlinear Studies, 2001)
The purpose of this paper is to develop comparison principles and study the existence and uniqueness of solutions for fuzzy differential equations under a more general condition than that of Lipschitz. Continuity of solutions as well as the global existence of the solution assuming local existence are also studied.